Magnetism of surfaces, interfaces, and nanoscale materials : Vol. 5 - Camley, Robert E.; Celinski, Zbigniew; Stamps, Robert L. (Amsterdam : Elsevier, 2016)
In the past 30 years, magnetic research has been dominated by the question of how surfaces and interfaces influence the magnetic and transport properties of nanostructures, thin films and multilayers. The research has been particularly important in the magnetic recording industry where the giant magnetoresistance effect led to a new generation of storage devices including hand-held memories such as those found in the ipod. More recently, transfer of spin angular momentum across interfaces has opened a new field for high frequency applications. This book gives a comprehensive view of research at the forefront of these fields. The frontier is expanding through dynamic exchange between theory and experiment. Contributions have been chosen to reflect this, giving the reader a unified overview of the topic.
""2.1. Infinitely Extended Flat Plate: In-Plane Field""""2.2. Spin Waves Propagating Perpendicular to the Surface, Conducting Films""; ""2.3. Surface Modes for Spin Waves Propagating Parallel to the Film Surface""; ""2.4. Infinitely Extended Flat Plate-Perpendicular-to-Plane Magnetization""; ""2.5. Nanostructures""; ""2.6. Antiferromagnets""; ""3. Examples of Experimental Characterization of Ferromagnetic Samples""; ""4. FMR Techniques""; ""4.1. Magnetic Damping""; ""4.2. Broadband FMR-Frequency Swept""; ""4.3. Broadband FMR-Field Swept""; ""4.3.1. Multimode Cavity Configuration""
Includes bibliographical references and index.
Print version record.
Keywords: Magnetic materials; Thin films -- Surfaces -- Magnetic properties; Interfaces (Physical sciences); SCIENCE -- Physics -- Magnetism; Interfaces (Physical sciences); Magnetic materials; Thin films -- Surfaces -- Magnetic properties; Electrical Engineering; Electrical & Computer Engineering; Engineering & Applied Sciences; Electronic books; Electronic books